Muslim Minority and Institutional Accessibility to Health Care Services in India:Reflections from the field - K. M. Ziyauddin (IJRDO - Journal of Social Science and Humanities Research, 2016)
This paper intends to focus on the relationship between communal violence and it impact on the accessibility of health care institutions among Muslim community. However attempt is also taken to explain the problems of accessibility beyond the dimension of communal violence. The paper is based on the empirical and sociological study of health condition of Muslims in the state erstwhile state of Andhra Pradesh. The study exposes the issues of availability and accessibility of health institution in a socio-cultural and political conditions namely during communal riots or communal outbreaks and at times terrorist attack elsewhere in any region of the Indian society and reveals the discrimination experienced at household level. The issue of access is a complex concept in the debate of public health services and at least four aspects require evaluation. If services are available and there is an adequate supply of services, then the opportunity to obtain health care exists, and a population may 'have access' to services. The extent to which a population 'gains access' also depends on financial, organizational and social or cultural barriers that limit the utilization of services. This study also tries to understand the availability and accessibility of health institutions across the three regions of erstwhile state Andhra Pradesh, i.e. Telangana, Coastal Andhra and Rayaseema. It is also noted that the availability of health institution in the state is comparatively better than some of the states but the specifically the accessibility with reference to Muslim population is subject of serious concern in the paper.